Pengembangan Buku Cerita Bergambar Materi Simbiosis Makhluk Hidup untuk Sekolah Dasar - Airindia zubaidah; Megawati Megawati; Zulqoidi R. Habibie (LPPM Universitas Muhammadiyah Muara Bungo, 2026)
Scientific literacy skills at the elementary school level require learning media that can present concepts concretely and in accordance with students' cognitive development. The symbiosis of living things is one of the third-grade science topics that is still abstract and requires concrete examples for easy understanding. Available textbooks tend to display few examples of images, resulting in students' poor understanding of the subject matter. Therefore, this research focused on developing an illustrated storybook that combines text, illustrations, and audiobooks that can be accessed via QR Code to increase students' understanding and interest in reading. This research is a type of Research and Development (R&D) using the 4D model which consists of four stages: Define, Design, Develop, and Disseminate. The Define stage was carried out by analyzing the needs of students and teachers. The Design stage included drafting the story script, designing illustrations, and integrating the audiobook with QR Code. The Develop stage involved producing the initial product and conducting validation by material experts, language experts, and media experts. The Disseminate stage was conducted through limited trials on third grade elementary school students and teachers to assess product practicality. The research instruments used were validation sheets, response questionnaires, and interview guidelines. The results showed that the developed picture storybook obtained an average validity score in the very valid category. The practicality test from both students and teachers resulted in a percentage above 90%, which was categorized as very practical. Thus, the final product in the form of a picture storybook equipped with an audiobook and QR Code is feasible to be used as a science learning medium in elementary schools. This media has been proven to facilitate students’ understanding of the concept of symbiosis and to foster reading motivation and active engagement in the learning process.